Dietary I(-) absorption: expression and regulation of the Na(+)/I(-) symporter in the intestine - Nicola, Juan Pablo (2015)
Thyroid hormones are critical for the normal development, growth, and functional maturation of several tissues, including the central nervous system. Iodine is an essential constituent of the thyroid hormones, the only iodine-containing molecules in vertebrates. Dietary iodide (I(-)) absorption in the gastrointestinal tract is the first step in I(-) metabolism, as the diet is the only source of I(-) for land-dwelling vertebrates. The Na(+)/I(-) symporter (NIS), an integral plasma membrane glycoprotein located in the brush border of enterocytes, constitutes a central component of the I(-) absorption system in the small intestine. In this chapter, we review the most recent research on structure/function relations in NIS and the protein's I(-) transport mechanism and stoichiometry, with a special focus on the tissue distribution and hormonal regulation of NIS, as well as the role of NIS in mediating I(-) homeostasis. We further discuss recent findings concerning the autoregulatory effect of I(-) on I(-) metabolism in enterocytes: high intracellular I(-) concentrations in enterocytes decrease NIS-mediated uptake of I(-) through a complex array of posttranscriptional mechanisms, e.g., downregulation of NIS expression at the plasma membrane, increased NIS protein degradation, and reduction of NIS mRNA stability leading to decreased NIS mRNA levels. Since the molecular identification of NIS, great progress has been made not only in understanding the role of NIS in I(-) homeostasis but also in developing protocols for NIS-mediated imaging and treatment of various diseases.